THE EFFECT OF SNAKES AND LADDERS GAME MEDIA COUNSELING IN IMPROVING STUDENTS' UNDERSTANDING OF THE VECTOR OF DANGUE HEMORRHAGIC FEVER IN SD NEGERI X KUTALIMBARU DELI SERDANG) - Meutia Nanda; Alya Az Zahra Sibuea; An’nas Tasya Rahmadhani; Muhammad Khair Gunawan; Uswataul Hasanah (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Dengue fever is a global health problem that remains a serious threat, especially in tropical countries like Indonesia. Children are the most vulnerable group to DHF infection due to an imperfect immune system and limited knowledge in prevention efforts. This study was conducted to determine the effect of counseling using snakes and ladders game media in improving student understanding. This study used a quantitative approach with a one group pre-test post-test design that aims to determine the difference in values between before and after counseling. The sample in the study amounted to 60 respondents with total sampling formula. Based on the results of the study, there is an effect of counseling using snakes and ladders game media to improve students' understanding of dengue disease vectors, this can be seen from the P-value of 0.000 <0.05 which indicates a significant difference between before and after counseling. With this activity can be influenced to increase knowledge of dengue disease prevention.